Improvement in workplace environment at a steel plant [electronic resource] - Kalsum Hidayah Ahmad Zaain, 1986- (2010)
Project Paper (Sarjana Muda Kejuruteraan (Mekanikal - Industri)) - Universiti Teknologi Malaysia, 2010